2017
DOI: 10.1371/journal.pone.0169438
|View full text |Cite
|
Sign up to set email alerts
|

Tonographic Effect of Ocular Response Analyzer in Comparison to Goldmann Applanation Tonometry

Abstract: AimsThe tonographic effect is a phenomenon of intraocular pressure (IOP) reduction following repeated tonometry. This study examines whether the tonographic effect occurs following IOP measurement performed with Ocular Response Analyzer (ORA).MethodsBoth eyes of 31 glaucoma patients and 35 healthy controls underwent nine IOP-measurements performed with GAT and ORA. The number of GAT and ORA measurements performed on each eye differed depending on the randomly allocated investigation scheme. Central corneal thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
(52 reference statements)
1
17
0
1
Order By: Relevance
“…According to the methodology of the EPIC-Norfolk Eye Study, both healthy eyes and eyes with glaucomatous damage were included in the analysis 9 . Previous studies have shown that CH is significantly lower in glaucomatous eyes 3 , 5 . A positive correlation found between CH and RNFL measurement in their study might at least partially be explained by the effect of glaucoma damage on CH and RNFL.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…According to the methodology of the EPIC-Norfolk Eye Study, both healthy eyes and eyes with glaucomatous damage were included in the analysis 9 . Previous studies have shown that CH is significantly lower in glaucomatous eyes 3 , 5 . A positive correlation found between CH and RNFL measurement in their study might at least partially be explained by the effect of glaucoma damage on CH and RNFL.…”
Section: Discussionmentioning
confidence: 79%
“…Corneal biomechanics has been an area of much recent interest as a risk factor for glaucoma development and progression 1 3 , 5 7 . In the present study, we aimed to evaluate the relationship between CH and quantitative measurements of the RNFL and optic disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No disturbance or damage to the cornea was observed. However, it is well known that some applanation tonometers produce the tonographic effect, which is a phenomenon in which IOP values decline with repeated tonometry (Stocker, 1958;Moses, 1961;Krakau and Wilke, 1971;Gaton et al, 2010;Zimmermann et al, 2017). In a study of repeated rebound tonometry in children, the tonographic effect did not occur (Dosunmu et al, 2014).…”
Section: Probe Positionmentioning
confidence: 98%
“…It was found that biochemical cornea properties influence the accuracy of applanation tonometry. 20,21 The ocular response analyzer [22][23][24][25] allows adjustment of IOP taking into consideration the biomechanical properties of the cornea. An alternative way of measuring IOP is by air puff tonometer.…”
Section: Introductionmentioning
confidence: 99%